Macro- and micro-galvanic corrosion of friction stir welding 6061-T6 Al and C1100 Cu dissimilar joints - Yi-Ting Wu; I-Chung Cheng; Chao-Sung Lin (Journal of Materials Research and Technology)
Friction stir welding (FSW) is one of the solid-state methods for welding dissimilar metals to inhibit the formation of intermetallic phases. The effect of the heterogeneous microstructures of FSW 6061-T6 Al and C1100 Cu dissimilar joints on corrosion in 3.5 wt % NaCl was studied, including macro- and micro-galvanic corrosions. The stir zone contained Cu particles embedded in Al, and CuAl2 and Cu9Al4 intermetallic phases formed via interdiffusion between Al and Cu. Consequently, the microstructure of the stir zone was heterogeneous. The Volta potential measurement revealed that Cu had a Volta potential of +200–400 mV relative to Al. An immersion test of the entire dissimilar joint revealed that the macro-galvanic coupling between 6061-T6 Al and C1100 Cu accelerated the corrosion of the stir zone. The stir zone tested individually showed that Al/CuAl2/Cu9Al4/Cu micro-galvanic coupling resulted in a uniform Al oxide/hydroxide layer on Al. Conversely, the surface of CuAl2 was porous and rich in Cu because of the dealloying of Al. The corrosion was not uniform and concentrated in Al-rich phases (Al, CuAl2). Moreover, the macro-galvanic couple between 6061-T6 Al and C1100 Cu base metals accelerated the corrosion of the heterogeneous stir zone. This study fills the gap between micro- and macro-galvanic corrosion of FSW Al and Cu dissimilar joints, which are essential for the applications.